Kemahiran Insaniah di IPTA Islam Malaysia dan Indonesia: Analisis dan Perbandingan - Lazim, Omar; Rahimin Affandi, Abd. Rahim; Nor Adina, Abd Kadir (2009)
Islamic institutions of higher learning, either owned by the government or by private companies are always subjected to negative interpretations. Graduates of these institutions are always described as not knowledgeable especially with development. They are always connected to the statement of just memorizing Islamic verses especially from Quran. This statement is no longer valid in the present day. These institutions always revise their curriculum parallel to contemporary development as practiced by usual institutions of higher learning by introducing new courses like management, economy, science and technology. It produces good results; graduates of Islamic institutions of higher learning are quite marketable in the job market nowadays. In order to enable them to be competitive with other graduates of institutions of higher learning, they enhance the soft skills of their students. In Indonesia and Malaysia, the basics of soft skills are introduced in the curriculum to enable the graduates to become more marketable. Both institutions are always looking for the best methodology to equip students with the soft skills during their academic learning. This study tries to compare the implementation of soft skills training between Islamic institutions of higher learning in Indonesia and Malaysia which includes the strengths and weaknesses of their approach.